The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1021/acs.analchem.7b04108
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Proteomics Enables Comparative Analysis of Brain Proteoforms Between Mouse Strains

Abstract: Over the past decade, advances in mass spectrometry-based proteomics have accelerated brain proteome research aimed at studying the expression, dynamic modification, interaction and function of proteins in the nervous system that are associated with physiological and behavioral processes. With the latest hardware and software improvements in top-down mass spectrometry, the technology has expanded from mere protein profiling to high-throughput identification and quantification of intact proteoforms. Murine syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
(77 reference statements)
2
29
0
Order By: Relevance
“…The results indicated that microproteins in different tissues were mostly related to tissue-specific functions ( Figure 5D ). For example, brain tissue has many microproteins related to nerves and hormones, which is consistent with previous research findings ( Marcus et al, 2004 ; Davis et al, 2018 ). Splenic tissue was rich in immunity-related microproteins, which is consistent with previous research ( Hu et al, 2018 ; Ma et al, 2019 ).…”
Section: Resultssupporting
confidence: 92%
“…The results indicated that microproteins in different tissues were mostly related to tissue-specific functions ( Figure 5D ). For example, brain tissue has many microproteins related to nerves and hormones, which is consistent with previous research findings ( Marcus et al, 2004 ; Davis et al, 2018 ). Splenic tissue was rich in immunity-related microproteins, which is consistent with previous research ( Hu et al, 2018 ; Ma et al, 2019 ).…”
Section: Resultssupporting
confidence: 92%
“…Labeling reagents are not needed in LFQ, so it can be applied to samples not grown in cell culture, such as patient tissue samples. LFQ has been applied to several larger scale studies of proteoform abundance changes across two conditions . The Kelleher lab first demonstrated this technique using yeast mutant versus wild‐type strains and quantified over 800 proteoforms.…”
Section: Quantification Of Proteoformsmentioning
confidence: 99%
“…Top-down proteomics is becoming increasingly applicable for the study of eukaryotic proteome and proteoforms [ 92 , 94 ]. It is also being used for the study of native prion-like proteins.…”
Section: Utilizing Proteomic Platforms To Understand Neurodegeneramentioning
confidence: 99%